Outcomes of school-aged children following traumatic brain injury from road traffic accidents in Malaysia: A retrospective study - Esther Jimbih; Mazlina Mazlan; Ria Waran; Vicknes Waran (PLoS ONE, 2026)
Background Traumatic brain injury (TBI) resulting from road traffic accidents (RTAs) is a leading cause of morbidity in children globally. However, paediatric TBI outcomes are understudied in Southeast Asia. Objective To examine functional outcomes and associated factors among school-aged children with RTA-related TBI in Malaysia. Methods This retrospective study analysed medical records of 542 children aged 7–17 years with first-time TBI from RTAs. Data on sociodemographics, injury characteristics, complications, and outcomes were collected. The subjects’ reports were grouped into three categories for analyses: young children (7–9-year-olds), adolescents (10–14-year-olds) and older adolescents (15–17-year-olds). Functional status was assessed using the Glasgow Outcome Scale–Extended for Paediatrics (GOS-E Peds), and reported as good (category 1 and 2) or poor (category 3–8) outcomes. Descriptive statistics and multivariate logistic regression were used. Results The majority of children were male (81.5%) with a mean age of 14.3 years. Motorcycles were the predominant accident mode (76.0%) especially among adolescents and older adolescents. The mean duration between the RTAs and report review was 20.7 ± 14.9 months. Only 27.5% of the children achieved good functional outcomes. Young children had the highest rate of recovery (34.5%), though not statistically significant. Among older adolescents, mild TBI significantly increased the odds of a good outcome (OR=2.5; 95% CI: 1.29–4.83; p = 0.007), while tracheostomy was strongly associated with poor outcomes (OR=7.02; 95% CI: 2.06–23.93; p = 0.002). Despite high rate of return to education, a significant proportion of children faced academic challenges post-brain injury. Conclusion Motorcycles remain the primary mode of RTA-related TBI among Malaysian children, particularly among adolescents. There was no significant difference in outcomes between the three age groups, although the young children had the highest rate of recovery. A substantial proportion of the children experience ongoing functional and academic difficulties despite returning to school. This highlights the need for coordinated clinical, educational, and policy responses in settings with limited paediatric rehabilitation infrastructure.